Analisis Pengaruh Financial Self Efficacy dan Financial Technology Terhadap Inklusi Keuangan - Anggraini, April Dwi; Trisnaningsih, Sri (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
This study aims to analyze the extent to which students' financial self-efficacy and utilization of digital financial technology impact their participation in formal financial services (financial inclusion). This study was conducted on students majoring in accounting at the National Development University “Veteran” of East Java, against the background of the urgency of increasing students' access to financial services in the digital age. The method used is a quantitative approach, by distributing questionnaires to 84 randomly selected students. The data was then processed using the Partial Least Square (PLS) technique with the help of SmartPLS 4.0 software. The research findings reveal that both students' confidence in managing finances and the use of financial technology such as e-wallets and digital banking applications, significantly increase students' chances of participating in formal financial services. In conclusion, the higher the confidence of students in financial matters and the more intensely they utilize financial technology, the greater their level of financial inclusion. This study provides crucial insights into how these two factors can encourage students' participation in the formal financial system.